2014
DOI: 10.1155/2014/248792
|View full text |Cite
|
Sign up to set email alerts
|

The Static Breaking Technique for Sustainable and Eco-Environmental Coal Mining

Abstract: The initiating explosive devices are prohibited in rock breaking near the goaf of the highly gassy mine. It is effective and applicable to cracking the hard roof with static cracking agent. By testing the static cracking of cubic limestone (size: 200 × 200 × 200 mm) with true triaxial rock mechanics testing machine under the effect of bidirectional stress and by monitoring the evolution process of the cracks generated during the acoustic emission experiment of static cracking, we conclude the following: the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Among them, the crushing process of the static crushing agent is slow, and the dosage of the crushing agent is not easy to control, which is difficult to ensure the accurate and rapid requirements of concrete crushing. 3,4 The vibration and dust problems caused by engineering blasting are more prominent, which has a great influence on the surrounding environment. 5,6 Mechanical crushing has high noise and low flexibility, and there are certain limitations for the parts that need accurate crushing.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the crushing process of the static crushing agent is slow, and the dosage of the crushing agent is not easy to control, which is difficult to ensure the accurate and rapid requirements of concrete crushing. 3,4 The vibration and dust problems caused by engineering blasting are more prominent, which has a great influence on the surrounding environment. 5,6 Mechanical crushing has high noise and low flexibility, and there are certain limitations for the parts that need accurate crushing.…”
Section: Introductionmentioning
confidence: 99%
“…He does this by using microscopic and electromagnetic analysis of the static and dynamic cracking of rocks. In order to further explore the properties of the static splinter-causing test object under stress through sound-release technology, Hao B. Y. and colleagues [21] employed genuine three-axis double-stress loading experiments. Laefer D. F. et al's [22] investigation of static fissures in various probe comparative intensities under the influence of ambient temperature revealed that raising ambient temperatures, lowering design comparative temperatures, and increasing melting temperatures would all hasten the expansion of the fissures.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to hydraulic fracturing which can produce a single fracture in the rock, multiple radial fractures can be observed around the injection borehole where the static expansive agent is used. Since the static expansive agent can produce a superior network of fractures, it has been applied to the rock fragmentation to enhance hard roof caving in underground mines [29]. However, the lack of knowledge about the static expansive agent controlled fracturing process is one of the main causes of its poor market value [14].…”
Section: Introductionmentioning
confidence: 99%